An Exponentially Distributed Stochastic Model for Sustainability Measurement of a Healthcare System - Khosravi, Faramarz; Izbirak, Gokhan; Adesina, Kehinde Adewale (Mdpi, 2019)
As the global environment is getting more competitive, sustainability is increasingly becoming an important assessment tool. An exponential distribution stochastic model is developed for the purpose of assessing and measuring the sustainability of healthcare system. The aim of this study is to provide a sustainability measuring model that is driven by the actual distribution status of the sustainability indicators. In this paper, the notions of the Triple Bottom Line (TBL) are followed in deriving the sustainability challenge and capacity indicators for the environmental, social, and economic indicators. Since basic challenges and capacities depend on the modes of the organization, the study proposes an exponentially distributed stochastic model for measuring sustainability. A numerical illustration of Iranian healthcare is presented to demonstrate the efficiency of the proposed model. In the results obtained, sustainability index for environmental, economic, and social are 54.40%, 48.80%, and 66.80% respectively. It indicates the healthcare achieved some sustainability through the social aspect; therefore, improving the environmental and economic aspect of the TBL is necessary. The proposed model can be used as a panoramic tool for effective measurement of the sustainability level of any healthcare system.
Keywords: Healthcare Sustainability; Triple Bottom Line; Exponentially distributed indicators; Performance measurement